Three Pass Protocol untuk Keamanan Kunci Berbasis Base64 pada XOR Cipher - Sulaiman, Oris Krianto; Nasution, Khairuddin; Siambaton, Mhd. Zulfansyuri (STIKOM Tunas Bangsa Pematangsiantar, 2020)
XOR cipher is a message randomization algorithm by performing XOR logical operations for plaintext and key so that it becomes a ciphertext. The problem lies in the predictable use of XOR. Therefore, it uses key security using the Three Pass Protocol. This protocol secures communication for each party. The key used for Three Pass Protocol communication is Base64. The Three Pass Protocol scheme for XOR Cipher key security using Base64 has a weakness because it is due to the Base64 encoding process which by default is easy for others to know. So that this research can be developed again to replace Base64 into a better algorithm in terms of security.